Effect of Vagal Nerve Stimulation on Cognitive Impairment Among Subjects with Anterior Cerebral Artery Syndrome: A Pilot Study. - S., Santhana Lakshmi; Srinivasan, Vignesh; Suganthirababu, Prathap; Kumar, Priyadharshini; Dhanusia S.; Kumaresan A.; Vishnuram, Surya (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Cognitive dysfunction, including impairments in attention, memory, executive function, and processing speed. This study was developed to determine the effectiveness of transcutaneous auricular vagal nerve stimulation on cognitive impairment among subjects with anterior cerebral artery syndrome. Purpose: The purpose of the study is to compare and evaluate the effectiveness of two non-pharmacological methods of treatment for cognitive impairment patients with ACA syndrome. Material and Methods: The project was conducted as a pilot study in a private hospital in Chennai. The experimental group (group A) received transcutaneous auricular vagal nerve stimulation for 20 minutes and conventional strengthening exercises for the affected limb for 10 minutes. Group B got conventional cognitive training (20 minutes) and strengthening exercises (10 minutes). Following the four-week treatment, a post-test analysis was performed using the Montreal cognitive assessment scale. Results: The post-test analysis obtained a mean value of about 27.25 and SD 1.5 for group A, whereas group B revealed 22.75 ± 1.25, mean ± SD, and a significant P value of 0.004. Conclusion: Non-invasive transcutaneous auricular vagal nerve stimulation has been proven to be an effective approach for preventing vascular dementia.